Accountability challenges confronting cyberspace governance - Jacqueline Eggenschwiler (Internet Policy Review, 2017)
Traditional, linear conceptions of account rendering bear little relevance in the realm of cyberspace governance, where accountability structures are often decentred. Building on existing accountability scholarship, this paper identifies key accountability challenges confronting cyberspace governance, including the problem of many hands, the profusion of areas, as well as the hybridity and malleability of institutional arrangements, and presents a set of policy recommendations geared towards addressing the latter. This paper holds that in order to address and mitigate the challenges identified, accountability relationships need to be consciously reframed and discursively constructed.
Keywords: 300; Cyber security; Governance; Policy challenges